Impact of Antimicrobial Resistance of Pseudomonas aeruginosa in Urine of Small Companion Animals in Global Context: Comprehensive Analysis - Ana Pereira; Telma de Sousa; Catarina Silva; Gilberto Igrejas; Patrícia Poeta (Veterinary Sciences)
The isolation of multidrug-resistant (MDR) bacteria from the urinary tracts of pets is increasingly common, particularly in animals with concurrent health conditions. Pseudomonas aeruginosa (PA) is one of the most significant antimicrobial-resistant bacteria affecting cats and dogs within the European Union (EU). This study aims to review the prevalence and antimicrobial resistance patterns of PA isolated from urine samples of small animals globally. This pathogen is known for its opportunistic infections and is a significant concern in veterinary medicine due to its inherent resistance to multiple antibiotics and its ability to acquire additional resistance mechanisms. This review seeks to enhance educational initiatives regarding the management of emerging MDR bacteria.